Environmental Degradation and its impacts on human health (Research, Society and Development, 2021)
Environmental degradation is one of the main problems today, discussed constantly by the World Environmental Protection Organizations. The erosion of some sustainable areas, the extinction of plant and animal species causes changes in the region's climatic phenomena in addition to the contribution to global warming. The objective of this study was to evaluate and present a diagnosis of environmental degradation of an area on the margins of the CE-292 in Crato - CE, caused by the action of man and its main socioenvironmental implications. In the beginning, the field visit was carried out. Then, information about the area was guided, such as: location, and the natural aspects and the main anthropic impacts that should be observed in the demarcated location. The acquired data were analyzed using the “Check List” methodology, in the descriptive modality, including the degrading actions and the observed impacts. With the study carried out, impacts of the abiotic, biotic and anthropic media were identified. Being listed impacts such as: deforestation, loss of biodiversity, proliferation of vectors that transmit diseases, erosion, property devaluation, visual pollution, gullies and invasion of exotic plants.